Tinjauan Yuridis Terhadap Perlindungan Hukum Bagi Konsumen Transaksi Jual Beli Online (Studi Jual Beli Online Di Bengkel Knalpot Burnout Exhaust) - Aldi Ferdiansyah; Eti Mul Erowati; Wiwin Muchtar Wiyono (Faculty of Law, Universitas Wijayakusuma, 2019)
Abstract To find out how the form of Juridical Review of Legal Protection for Consumers Online Buy and Sell Transactions, and to explore various aspects of issues that have been formulated in the formulation of problems. To achieve these objectives the author uses a normative juridical approach. The research specifications used are descriptive research. The data method is presented in the form of descriptions which are arranged systematically. The condition of e-commerce on the one hand brings benefits mainly due to efficiency, but on the other hand brings doubt especially to legal issues regarding legal certainty of Consumer Protection and the validity of business transactions. as stipulated in Article 1 paragraph 1 of Act No. 8 of 1999 concerning Consumer Protection which states that